1959
DOI: 10.1039/tf9595501826
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular forces in quasi-spherical molecules. Part 2

Abstract: The collision integrals necessary for the calculation of transport coefficients of gases have been computed for an intermolecular potential of the form 4(r) = A/+ -B/r7, where r is the distance between molecular centres. These integrals have been used in combination with existing second virial coefficient computations to test the suggestion that the 28 : 7potential describes the form of the intermolecular interactions which may be considered to occur between the centres of quasi-spherical molecules such as CF4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1969
1969
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For SF6, two 28-7 Lennard-Jones potentials due to McCoubrey and Singh [14] and Powles et al [15] were available. Neumann [16] had developed a numerical potential to which we fitted an analytic expression of the HFD form: have developed modern potentials in the M3SV form [17,18].…”
Section: Calculation Of Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…For SF6, two 28-7 Lennard-Jones potentials due to McCoubrey and Singh [14] and Powles et al [15] were available. Neumann [16] had developed a numerical potential to which we fitted an analytic expression of the HFD form: have developed modern potentials in the M3SV form [17,18].…”
Section: Calculation Of Spectramentioning
confidence: 99%
“…The calculations have been performed with a 28-7 Lennard-Jones potential[14]. Downloaded by [McGill University Library] at 03:…”
mentioning
confidence: 99%
“…One of the first studies done by Henry et al[42] examined viscosity data reported for other fluids near the critical point (xenon, CO, argon, krypton, nitrogen, oxygen, ethane, methane, and propane) and established a relation for the corresponding states. Combining results from[42] with the low-density SF 6 viscosity data[43,44] yields η(ρ c , T c ) ≈ 3.47 × 10 −5 P a • s[45,46]. Wu and Webb[46] found that for a reduced temperature range of1.22 × 10 −4 ≤ ≤ 6.90 × 10 −2 , there is no critical anomaly in share viscosity of SF 6 and η = (425 + 14.5(T c − T ) ± 15) × 10 −7 P a × s. A recent review of SF 6 data by Guder and Wagnera [47] used the following critical point values T c =(318.7232 ± 0.0020) K, p c =(3.754 983 ± 0.000 200) MPa, and…”
mentioning
confidence: 99%
“…The calculated average of the square of the anisotropy can be approximately doubled by computing the thermal average using one of the modified LennardJones pair potentials for SF6 [23][24][25], thus substantially reducing the discrepancy between experimental and calculated values (see table 3 for a comparison of results with different potentials). Smaller but significant dependence of calculated depolarized light scattering intensities [26], depolarization ratios [11], and second Kerr virial coefficients [16] on the choice of pair potential has been reported previously.…”
Section: = %~---Tmentioning
confidence: 99%